Lama Penyimpanan Air Susu Ibu (ASI) Memengaruhi Kandungan Zat Gizi Dalam ASI - Handayani, Sri; Riezqy Ariendha, Dian Soekmawaty; Pratiwi, Yopi Suryatim (Universitas Qamarul Huda Badaruddin, 2019)
The condition in which the mother works is one of the conditions that inhibits breastfeeding. In order for women to work, they can still provide breast milk, so milking and storage are needed. The storage process can preserve breast milk for some time. The existence of a long treatment of breast milk storage is suspected to cause physical changes and chemical composition. Based on several research results, it can be concluded that the duration of breast milk storage both in the refrigerator and freezer will affect the amount of fat and protein content in breast milk. The cause of fat damage is divided into three groups, namely damage due to oxidation, the presence of enzymes, and fat hydrolysis reaction. Changes in protein levels of breast milk during storage may be caused by the process of proteolysis and protein denaturation.